Subglacial cavity collapses on Swiss glaciers: Spatiotemporal distribution and mass loss contribution - Leo Hösli; Christophe Ogier; Andreas Bauder; Matthias Huss; Mauro A. Werder; Mylène Jacquemart; Elias Hodel; Darrel A. Swift; Aaron Cremona; Jane Walden; Daniel Farinotti (Journal of Glaciology)
Glacier collapse features, linked to subglacial cavities, are increasingly common on retreating Alpine glaciers. These features are hypothesized to result from glacier downwasting and subsurface ablation processes but the understanding regarding their distribution, formation and contribution to glacier mass loss remains limited. We present a Swiss-wide inventory of 223 collapse features observed over the past 50 years, revealing a sharp increase in their occurrence since the early 2000s. Using high-resolution digital elevation models, we derive a relationship between collapse feature area and ice ablation and estimate the Swiss-wide contribution of collapse features to glacier mass loss to be $19.8× 10^6\,\text{m}^3$ of ice between 1971 and 2023. Based on extensive observations at Rhonegletscher, including surface displacement, ground-penetrating radar and drone-based elevation models, we quantify subsurface ablation rates of up to 27 cm d−1 and provide a detailed description of the collapse processes. We propose that glacier downwasting, enhanced energy supply through subglacial conduits and locally increased basal melt are key components to subglacial cavity growth. Our results highlight the importance of collapse features in the ongoing retreat of Alpine glaciers, stressing the need for further research to understand their formation and long-term implications for glacier dynamics under climate change.